A study of social capital: how much do relationships matter in farmland leasing? - Pitts, Allison Leigh (Kansas State University, 2019)
Social capital is important in many business relationships, the agricultural sector especially. With almost 40% of the farmland in the United States leased from someone else, these relationships are an integral part of many farming operations. In this paper, social capital can be thought of as the idea that a person’s relationships can impact economic outcomes. The goal of this study is to find the impact of social capital on farmland leasing relationships in Kansas, using data from a survey sent to both producers and landowners. The survey was sent to members of the Kansas Farm Management Association (KFMA) in late January 2018, with the receiving period ending in mid-May 2018. The survey provided data on the rental rate of farmland, characteristics of the lease, the land and the relationship between the producer and landowner. Utilizing a snowball method, a second survey was given to the producer to send to their landowner with the intention of collecting a database of matched pairs. An OLS regression was used to analyze producer data to determine the impact of producer characteristics, landowner characteristics and land characteristics on cash rental rates. Various factors such as lease length, a family relationship, land productivity, how the landowner obtained the land and the location of the land were thought to impact the rental rate paid to the landowner in a cash rent lease. However, results estimate that doubling the length of lease may result in a 9% discount on the rental rate as compared to market value and that if the landowner inherited the land there could be up to a 15% discount on the rental rate as compared to market value. As well as the fact that productivity of the land has a positive effect on rental rate, meaning more productive land will cost more to rent. This supports the hypothesis that longer leasing relationships, those with higher social capital, have a negative impact on rental rate paid to the landowner. It disproves the hypothesis that when land changes hands from one landowner to the next, the previous social capital is lost, instead it appears that the relationships continue unaffected. These results present an opportunity to better prepare landowners and producers for conversations about farmland leasing. For producers who rely on leased land, being aware of current relationships and their value is important, as well as knowing how to have conversations about estate planning. For beginning farmers, this information can be used as a building block, in place of monetary capital they may not have. Being able to form strong relationships with the people around them can prove to have value in the future. The results show that social capital has a significant impact on farmland rental rates in Kansas.
Keywords: Agriculture Economics; Social Capital; Leasing